Peroneal Muscle Size and Quality Changes after Impairment-Based Rehabilitation in Patients with Chronic Ankle Instability - Abbis Jaffri; Rachel Koldenhoven; Alexandra Lempke; Joseph Park; Joe Hart; Jay Hertel; Susan Saliba (International Journal of Sports Physical Therapy, 2026)
Background Peroneal muscles are the primary stabilizers against ankle inversion movements associated with lateral ankle sprains. Individuals with chronic ankle instability (CAI) demonstrate peroneal muscle deficits including decreased strength, slower nerve conduction velocity, and reduced cross-sectional area. Ultrasound (US) imaging provides a valid, cost-effective method to assess peroneal muscle size and quality following rehabilitation. Hypothesis/Purpose To determine peroneal muscle size and quality changes using US imaging following impairment-based rehabilitation in patients with CAI. Study Design Prospective cohort study. Methods Twenty-six patients with CAI (age: 21.9 ± 3.5 years; 18 females, 8 males) completed an 8-session, 4-week impairment-based rehabilitation program addressing range of motion, balance, strength, and functional performance deficits with emphasis on peroneal activation exercises. US imaging assessed peroneal muscle cross-sectional area (CSA) in sidelying and bipedal stance positions and echogenicity (a measure of muscle quality) in bipedal stance for both limbs before and after rehabilitation. Paired t-tests were used to compare pre- and post-rehabilitation values. Results Significant (p < 0.01) increases in CSA were observed in the trained limb during sidelying (3.44 ± 0.99 to 3.72 ± 0.98 cm²) and bipedal stance (3.46 ± 1.05 to 4.31 ± 0.98 cm²) positions. Similar CSA increases occurred in the untrained limb. Echogenicity significantly decreased in the trained limb (70.2 ± 9.91 to 65.7 ± 8.68, p = 0.01), indicating improved muscle quality, with no significant changes in the untrained limb. Conclusion An 8-session, 4-week impairment-based rehabilitation program resulted in significant peroneal muscle CSA increases in patients with CAI, with cross-education effects observed in the untrained limb. Muscle quality, as measured by echogenicity, improved in the trained limb, supporting neuromuscular benefits of targeted rehabilitation. Impairment-based rehabilitation should be incorporated into CAI management programs. Level of Evidence 3